I'm Sorry "About That": Apologies, Indexicals, and (Unnamed) Offenses. Issue 1 (2nd January 2016) - Margutti, Piera; Traverso, Véronique; Pugliese, Rosa
Abstract : We investigate an apology format, "I'm sorry about it/that, " where indexical terms (pronouns) refer to the offense rather than naming it. We identified two subsets in our collection of indexical apologies. In one, indexicals are subsequent either to the offense formulation or to an apology-relevant event; in the second, indexicals are used without any prior named offense. We found these two uses are associated to distinct contextual features. In the first set, apologizers also initiate the course of action, making relevant the apology; in the second, would-be apologizers find themselves at fault during/because of the call and apologize in response to a course of action initiated by the virtual offended person. Here indexicals draw their meaning from prior talk, serving speakers' interactional needs, when apologizing is problematic. More specifically, speakers manage to apologize without specifying the offense, often rejecting their responsibility for the virtual or actual offense.